The Effect of Nutritional Management in the Nutritional Status of Patients with Pulmonary Tuberculosis: A Systematic Review Literature - Sagala, Adi Brando M; Rekawati, Etty; Nursasi, Astuti Yuni (Indonesian Journal of Global Health Research, 2024)
Pulmonary Tuberculosis (TB) incidence and mortality rates in 2021 are higher than in 2020. The main risk factor for TB is malnutrition. Conversely, TB patients with malnutrition will experience obstacles in the healing process. The aim of this study was to review the results of research on the effect of nutritional management on the nutritional status of clients. The study design was a systematic literature review with PRISMA protocol. The literature search was limited to the last 10 years (2013-2023) in six databases, namely: Pubmed, Proquest, Science Direct, Scopus, Sage Journal, Wiley, and supplemented with hand searched in Google Scholar. All literature obtained has been reviewed for quality by each researcher using the Joanna Bridge Institute checklist for critical appraisal, then summarizing evidence, and interpreting the results. The initial search obtained 2688 literatures. The final result was seven literatures in this study. The results of these studies show that nutritional management has a positive effect on the nutritional status of TB patients. The types of nutrition management activities are individual diet, provision of high-calorie and high-protein supplementary foods, nutrition counseling, and supplementation. It was concluded that the intervention of individualized diet preparation had a statistically significant effect on improving nutritional status.